Pars Plana Vitrectomy in Posttraumatic Endophthalmitis in Cipto Mangunkusumo Hospital Indonesia - Andi Arus Victor; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani Adriono; Anggun Rama Yudantha; Mario Marbungaran Hutapea (Indonesian Vitreoretinal Society, 2020)
Introduction: Endophthalmitis is an inflammation of the intraocular tissues and fluid, and an emergency in ophthalmology. One of the most common causes of endophthalmitis is post-traumatic endophthalmitis. Post-traumatic endophthalmitis has a poorer prognosis than post-cataract surgery endophthalmitis. The immediate pars plana vitrectomy (PPV) surgery in post-traumatic endophthalmitis is beneficial for optimizing of final visual. Methods: A retrospective descriptive study of post-traumatic endophthalmitis patients underwent pars plana vitrectomy in the Ciptomangunkusumo Hospital, Indonesia from January 2017 – June 2017. Result: There were twelve cases of post-traumatic endophthalmitis undergoes pars plana vitrectomy within the period of January 2017-June 2017. The most frequently identified causative organism was Staphylococcus (33,3%). There was an improvement of final visual acuity after the procedure of pars plana vitrectomy in 58.3% post-traumatic endophthalmitis patients. Conclusion: Early PPV leads to vision improvement and maintains visual acuity in post-traumatic endophthalmitis. Keywords: Pars Plana Vitrectomy, Endophthalmitis, Post-traumatic